2013
DOI: 10.1007/s00264-013-2140-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved kinematics of total knee replacement following partially navigated modified gap-balancing technique

Abstract: Purpose Navigation-based total knee arthroplasty (TKA) has proven its value for restoration of the limb axis. However, patient-orientated results after TKA show a wide variation from the correct implantation technique. Nonphysiological kinematics without posterior femoral rollback and tibial internal rotation in flexion could be one reason for this. We postulated that a modified gap-balancing technique with navigation of the tibia alone, in comparison to a conventional navigated technique, would: (1) obtain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
(46 reference statements)
1
17
1
Order By: Relevance
“…However, such a great influence of sagittal component alignment on patellar kinematics was not conceivable. While some recent investigations have described the influence of sagittal component alignment on tibiofemoral kinematics ( Fitz et al 2012 , Baier et al 2014 , Gromov et al 2014 ), we could not find any study on its influence on patellar kinematics in the current literature. The impact of sagittal component alignment could be explained by changed parapatellar soft tissue tension and tibiofemoral contact points.…”
Section: Discussioncontrasting
confidence: 58%
“…However, such a great influence of sagittal component alignment on patellar kinematics was not conceivable. While some recent investigations have described the influence of sagittal component alignment on tibiofemoral kinematics ( Fitz et al 2012 , Baier et al 2014 , Gromov et al 2014 ), we could not find any study on its influence on patellar kinematics in the current literature. The impact of sagittal component alignment could be explained by changed parapatellar soft tissue tension and tibiofemoral contact points.…”
Section: Discussioncontrasting
confidence: 58%
“…This behavior has also been observed in studies analyzing the effect of native laxities in various knee flexion angles 48 and their relationship with alignment, especially when following, as we did, a gapbalancing technique. 19,21 After surgery, we could not find any statistically significant differences among the different PDPs. It is remarkable to mention that, despite the PDP, it is more difficult to achieve a postoperative "within-range" dynamic alignment as the knee bends.…”
Section: Discussionmentioning
confidence: 71%
“…[17][18][19][20] It is a powerful instrument for intraoperatively supporting and guiding the surgeon in the adequate postoperative soft tissue balance of the knee. 17,[21][22][23][24] Through this technology, the authors have published that there is well-defined preoperative dynamic alignment in osteoarthritic knees. 16 The purpose of this study was to determine the dynamic coronal HKA angle after MA in total knee replacement using computer navigation.…”
mentioning
confidence: 99%
“…Four comparative studies reported outcomes of KSS and FKSS scores [9,[11][12][13]. One RCT reported outcomes of sixmonth KSS, and one RCT reported outcomes of six-month FKSS.…”
Section: Patient-reported Outcomesmentioning
confidence: 99%